1981
DOI: 10.1007/bf00442098
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of mortality rate in premature infants by substitution of thyroid hormones

Abstract: Note from the Editors. Although Abstract. Our previous examinations had shown that 9 of 13 premature infants with severe respiratory distress had hypothyroid T4-values. On the basis of these results a prospective study was initiated. Every second neonate born after less than 37 weeks gestation or weighing less than 2200 g and admitted to our intensive care unit since Janary 1979 received a prophylactic dose of 25 gg L-Thyroxine and 5 lag Tri-iodothyronine daily. Five of the patients inadvertently did not rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…In addition, T 3 enhances expression of the type I deiodinase gene (27), and T 3 treatment thus could increase endogenous T 3 production. It may, however, be difficult to find an appropriate T 4 /T 3 regimen, because a middle course must be found between a T 3 dose by which maturation is enhanced and morbidity is decreased (33,34), and a T 3 dose that does not increase protein catabolism (35). Treatment with T 3 alone is not advisable, as it will result in lower plasma T 4 concentrations by negative feedback (19), and thus will increase the risk of depletion of cerebral thyroid hormone supply.…”
Section: European Journal Of Endocrinology (1998) 139mentioning
confidence: 99%
“…In addition, T 3 enhances expression of the type I deiodinase gene (27), and T 3 treatment thus could increase endogenous T 3 production. It may, however, be difficult to find an appropriate T 4 /T 3 regimen, because a middle course must be found between a T 3 dose by which maturation is enhanced and morbidity is decreased (33,34), and a T 3 dose that does not increase protein catabolism (35). Treatment with T 3 alone is not advisable, as it will result in lower plasma T 4 concentrations by negative feedback (19), and thus will increase the risk of depletion of cerebral thyroid hormone supply.…”
Section: European Journal Of Endocrinology (1998) 139mentioning
confidence: 99%
“…In a case control study Eggermont et al treated 10 premature infants with a mean GA of 28.7 weeks with 5 mg/kg/d of T 3 during 6 weeks (29). Scho Ènberger et al (30) studied the effect of the combined treatment with T 4 (25 mg) and T 3 (5 mg) in 45 premature infants in a quasi-randomized manner. Both studies used much higher doses of T 3 , and administered T 3 on a daily basis during a period of time.…”
Section: Discussionmentioning
confidence: 99%
“…The sample sizes in the subgroups are too small to draw definite conclusions. The only trial to have shown any overall benefit is one in which both T 4 and T 3 were given together (38). In this trial the mortality was reduced from 29% to 6.6%, but the results must be interpreted with caution because the study population included any baby less than 37 wk gestation and only 11% of the treated group and 16% of the untreated group were Ͻ 31 wk.…”
Section: Table 3 Adverse Effectsmentioning
confidence: 95%